Genome‐wide association study identifies genomic regions of association for cruciate ligament rupture in Newfoundland dogs. (16th May 2014) - Baird, A. E. G.; Carter, S. D.; Innes, J. F.; Ollier, W.; Short, A.
Summary Cranial cruciate ligament rupture (CCLR) is the most common cause of pelvic limb lameness in dogs. To investigate the genetic basis of canine CCLR, we conducted a genome‐wide association study using a canine SNP array in Newfoundland pedigree dogs with and without CCLR (n = 96). We identified three main chromosomal regions of CCLR association (on chromosomes 1, 3 and 33). Each of these regions was confirmed by Sequenom genotyping in a further cohort of Newfoundlands (n = 271). The results, particularly SNPs identified in the SORCS2 and SEMA5B genes, suggest that there may be neurological pathways involved in susceptibility to canine CCLR.